2021
DOI: 10.1186/s13068-021-02074-x
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of multiple enzymes from industrial Aspergillus niger strain O1 on starch saccharification

Abstract: Background Starch is one of the most important renewable polysaccharides in nature for production of bio-ethanol. The starch saccharification step facilitates the depolymerization of starch to yield glucose for biofuels production. The filamentous fungus Aspergillus niger (A. niger) is the most used microbial cell factory for production of the commercial glucoamylase. However, the role of each component in glucoamylases cocktail of A. niger O1 for starch saccharification remains unclear except … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…While this manuscript was in revision, two papers regarding the strain engineering of A. niger N1 [ 71 ] and O1 [ 72 ] using the protoplast transformation procedure described in M. thermophila were published. In A. niger O1, Guo et al described that the four overexpression and four knockout transformants of the acid α-amylase gene were simply obtained after protoplast transformation, while four overexpression and two knockout transformants of the neutral α-amylase gene were generated [ 72 ]. In A. niger N1, 6 out of 52 transformants were triple-gene mutants, with a gene editing efficiency of 11.5% [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While this manuscript was in revision, two papers regarding the strain engineering of A. niger N1 [ 71 ] and O1 [ 72 ] using the protoplast transformation procedure described in M. thermophila were published. In A. niger O1, Guo et al described that the four overexpression and four knockout transformants of the acid α-amylase gene were simply obtained after protoplast transformation, while four overexpression and two knockout transformants of the neutral α-amylase gene were generated [ 72 ]. In A. niger N1, 6 out of 52 transformants were triple-gene mutants, with a gene editing efficiency of 11.5% [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…In A. niger N1, 6 out of 52 transformants were triple-gene mutants, with a gene editing efficiency of 11.5% [ 71 ]. Compared to previous studies [ 71 , 72 ], the PMT method we developed here is relatively simple. First, in previous studies, the young mycelia were washed twice with 1 mol/L MgSO 4 before lysing with enzymatic hydrolysate [ 71 , 72 ], while in our study, enough protoplasts could be obtained without carrying out these washing steps; therefore, the PMT method that we developed is relatively simple and saves time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…* * P < 0.01 (Student's t-test), * P < 0.05 (Student's t-test), n.s., not significant. most abundant protein in the secretomes of 2-day, 4-day, 6day cultures (Guo et al, 2021). Peptide search analyses revealed that A2QAC1 (UniProt accession) was the most abundant αglucosidase, ranked fifth among all detected proteins in the O1 secretome.…”
Section: Identification Of Genes Related To Transglycosylation Activi...mentioning
confidence: 99%